2020
DOI: 10.5539/ijbm.v15n7p108
|View full text |Cite
|
Sign up to set email alerts
|

The Stressful Implications of Remote E-Working: Evidence from Europe

Abstract: This paper investigates the importance of different modes of spatial flexibility as well as of the distinction between autonomy and discretion to find plausible explanations of the so-called autonomy paradox, which maintains that the more the job autonomy that remote e-workers have the greater the effort they put into their work with adverse effects on work-related stress. Using multiple regressions, we test the hypotheses regarding the direct influence of autonomy, discretion and work intensification as well … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 28 publications
(46 reference statements)
2
17
0
Order By: Relevance
“…On the other hand, telework can lead to unclear boundaries between work and personal life, increased work demands, the depersonalization of relationships at work, a lack of clarity in job roles, and adverse effects on individual wellbeing. Several studies highlight that teleworkers experience greater work intensification, frequent work interruptions, long working hours, lack of recovery time, and more demands to work during one’s free time, at high speed and to tight deadlines, inducing stress and diminishing teleworkers’ wellbeing [ 5 , 14 ]. According to border theorists, the achievement of work–life balance is more difficult where the borders between home and work are intentionally blurred, as is the case for teleworkers [ 23 ].…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
See 4 more Smart Citations
“…On the other hand, telework can lead to unclear boundaries between work and personal life, increased work demands, the depersonalization of relationships at work, a lack of clarity in job roles, and adverse effects on individual wellbeing. Several studies highlight that teleworkers experience greater work intensification, frequent work interruptions, long working hours, lack of recovery time, and more demands to work during one’s free time, at high speed and to tight deadlines, inducing stress and diminishing teleworkers’ wellbeing [ 5 , 14 ]. According to border theorists, the achievement of work–life balance is more difficult where the borders between home and work are intentionally blurred, as is the case for teleworkers [ 23 ].…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…In sum, although an extensive body of research discussing this autonomy paradox associated with telework already exists, potential explanations are still limited [ 29 ]. The literature suggests that one way to engage more thoroughly with the autonomy paradox is to distinguish between different types of teleworkers based on the location from where they work [ 31 ], yet few studies attempt to test this hypothesis [ 6 , 14 , 17 , 32 ]. Therefore, our investigation takes the variability among the various types of remote workers as a main dimension of analysis, as recent research has shown that the level of mobility and the intensity of ICT use varies across telework arrangements, and it has a significant influence on working conditions.…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
See 3 more Smart Citations